Nominal restatement - Jasinskaja, Ekaterina (Proceedings of Sinn und Bedeutung, 2019)
This paper identi?es, explores and provides a formal analysis to a phenomenon that I will call nominal restatement. Nominal restatement (NR) bears a certain similarity to nominal apposition (NA). However, whether an equality sign can be put between these notions depends largely on our assumptions about the range of facts pertaining to apposition, which is not a matter of perfect consensus. This paper shows that NR goes beyond the notion of NA developed by Potts (2005) and is not covered by his analysis. It also presents a purely pragmatic account of NR in terms of the discourse relation of restatement (Jasinskaja 2006b), which both explains the new observations concerning NR (e.g. quanti?cation and scope behaviour) and provides a better explanation to some old observations about NA that are also valid for NR (e.g. case). Finally, I address the question whether the notion of NA can ultimately be done away with by subsuming it under the more general notion of NR and discuss some related problems.